Analisis Semiotika John Fiske Mengenai Aging Masculinity pada Film Sejuta Sayang Untuknya - Rizki, Wahyu Pratama; Rahmawati, Aulia (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The aging process always happens to men or women regardless of sex or gender. One of the things that is always attached and related to gender is masculinity. The definition of masculinity is a culturally influenced social thought and practice about how to shape male traits. The hegemony of masculinity that is dominated by young men causes masculinity in older men to be considered demasculinized or the loss of masculinity. The depiction of aging masculinity in Indonesian film media has recently dared to break the stigma of masculinity dominated by young men. One of the Indonesian films, Sejuta Sayang Untuknya, directed by Herwin Novianto, tells about family issues regarding the struggle of an elderly single father in raising and caring for his only daughter amid economic difficulties. This research uses a descriptive qualitative approach with John Fiske's semiotic analysis method to convey codes and deep meanings in the movie. The researcher's goal is to represent how aging masculinity in the movie Sejuta Sayang Untuknya, especially in the character of Aktor Sagala as a single father. The results of this study found that there are 6 scenes related to twilight masculinity analyzed using John Fiske's three stages of semiotics including the level of reality, level of representation, and level of ideology. Keywords: Representation, Aging Masculinity, John Fiske Semiotics, Film.